2011
DOI: 10.1093/toxsci/kfr142
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl Sulfonates Cause Alkyl Chain Length–Dependent Hepatic Steatosis and Hypolipidemia Mainly by Impairing Lipoprotein Production in APOE*3-Leiden CETP Mice

Abstract: Perfluorobutane sulfonate (PFBS), perfluorohexane sulfonate (PFHxS), and perfluorooctane sulfonate (PFOS) are stable perfluoroalkyl sulfonate (PFAS) surfactants, and PFHxS and PFOS are frequently detected in human biomonitoring studies. Some epidemiological studies have shown modest positive correlations of serum PFOS with non-high-density lipoprotein (HDL)-cholesterol (C). This study investigated the mechanism underlying the effect of PFAS surfactants on lipoprotein metabolism. APOE*3-Leiden.CETP mice were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 52 publications
15
102
1
2
Order By: Relevance
“…Membrane transport may also play an important role if cholesterol and PFAAs share common processes or are influenced by common factors. Bijland et al (2011) observed that dietary PFOS increased expression of PFOS genes involved in fatty acid uptake and transport in APOE n 3-Leiden.CETP mice. Watkins et al (2013) found that among four PFAAs (PFOA, PFNA, PFHxS, and PFOS), only PFOS was associated with LINE-1 DNA methylation, which is known to regulate gene expression and may influence serum lipids (Nelson et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Membrane transport may also play an important role if cholesterol and PFAAs share common processes or are influenced by common factors. Bijland et al (2011) observed that dietary PFOS increased expression of PFOS genes involved in fatty acid uptake and transport in APOE n 3-Leiden.CETP mice. Watkins et al (2013) found that among four PFAAs (PFOA, PFNA, PFHxS, and PFOS), only PFOS was associated with LINE-1 DNA methylation, which is known to regulate gene expression and may influence serum lipids (Nelson et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Nuclear receptors play a key role in lipid metabolism and adipogenesis, raising the concern that PFAAs may disrupt lipid regulation (Maher et al, 2008;Fang et al, 2012). In addition, another study utilizing the APOEn3-Leiden.CETP mouse model showed that PFOS may reduce TC by impairing lipoprotein production (Bijland et al, 2011). Compared with the effects found in animals, studies in humans have reported inconsistent associations between PFAAs and serum lipids (Frisbee et al, 2010a;Nelson et al, 2010;Fisher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…36 Using the APOE*3-Leiden.CETP mouse model that has an attenuated clearance of apolipoprotein B-containing lipoproteins and exhibits human-like lipoprotein metabolism when fed a Western-type diet, Bijland et al 36 reported that serum PFOS concentrations (range, 85,600 to-to 124,700 ng/mL) resulted in markedly lowered plasma triglycerides and lower lipoprotein levels (VLDL and HDL). Gene expression data suggested that these effects were mediated largely by PPARα and PXR.…”
Section: Toxicologic Evidencementioning
confidence: 99%
“…per day to male mice (APOE*3-Leiden.E3L CETP) for 4-6 weeks, reduced triglycerides, cholesterol, non-high density lipoprotein, high density lipoproteincholesterol, plasma ApoA1, low density lipoprotein, apoB production, free fatty acids and glycerol and increased lipase activity and clearance of triolein (Bijland et al, 2011).…”
Section: Repeat Dose Toxicitymentioning
confidence: 95%
“…per day for 4-6 weeks was reported to reduce plasma triglycerides, cholesterol and increase clearance of triolein (Bijland et al, 2011).…”
Section: Repeat Dose Toxicitymentioning
confidence: 98%